Differential changes in sphingolipids between TNF-induced necroptosis and apoptosis in U937 cells and necroptosis-resistant sublines. Issue 9 (September 2015) - Sawai, Hirofumi; Ogiso, Hideo; Okazaki, Toshiro
Highlights Changes in sphingolipids in necroptosis were investigated using mass spectrometry. The ceramide level in necroptosis was twice as high as that in apoptosis after 4 h. An increase in PI-positive cells was observed only in necroptosis within 4 h. BHA inhibited increases in ceramide levels in necroptosis but not in apoptosis. The ROS-induced large increase in ceramide levels may play a role in necroptosis.